2008
DOI: 10.1111/j.1439-0507.2008.01490.x
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of a protein purified from the latex of Hevea brasiliensis on oral microorganisms

Abstract: This study aimed at screen for antimicrobial activity present in the non-rubber constituents of rubber latex of Hevea brasiliensis against various microbial strains. An antimicrobial protein, hevein was extracted from the bottom fraction after centrifugation and purified by acetone fractionation and anion exchange chromatography on a DEAE-Sepharose Fast Flow column. This procedure was more efficient and rapid than the previously described procedures. The antimicrobial activity was investigated and revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 21 publications
0
45
0
Order By: Relevance
“…In a matter of fact, twenty-five per cent of the proteins in C-and B-serums are known as antimicrobial agents in Hevea brasiliensis. Most of these proteins have the activity of chitinase/lysozyme which can degrade fungal and bacterial cell wall components such as chitin and peptidoglycan, respectively [8,11]. However, among these known proteins, small size proteins known as protease inhibitor were less studied in Hevea latex.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a matter of fact, twenty-five per cent of the proteins in C-and B-serums are known as antimicrobial agents in Hevea brasiliensis. Most of these proteins have the activity of chitinase/lysozyme which can degrade fungal and bacterial cell wall components such as chitin and peptidoglycan, respectively [8,11]. However, among these known proteins, small size proteins known as protease inhibitor were less studied in Hevea latex.…”
Section: Introductionmentioning
confidence: 99%
“…Limited numbers of research have reported the isolation and characterization of protease inhibitor from the latex of two Hevea tree clones RRIM 600 and PB 260 [11][12][13][14][15]. In molecular levels, high numbers of Expressed Sequence Tags (ESTs) encoding protease inhibitors were predicted in laticifers [10].…”
Section: Introductionmentioning
confidence: 99%
“…According to our current knowledge, the protein with the most prospective application is hevein for antimicrobial or antifungal agents [7,70]. The other protein with potential application is the 43 kDa patatin-homologue [10,12], due to its similarity with patatin.…”
Section: Latexmentioning
confidence: 99%
“…Isolation and characterization of protease inhibitors from various plant species have been carried out using affinity column chromatography (Bijina et al, 2011;Popovic et al, 2013;Al-Assadi, 2013, Bunyatang et al, 2013Chaudhary et al, 2008;Sabotič et al, 2012). In H. brasiliensis, several types of protease inhibitors have also been successfully extracted from latex (Bangrak & Chotigeat, 2011;Kanokwiroon et al, 2008;Sritanyarat et al, 2006). Bunyatang et al (2013) has demonstrated the inhibitory activity of Hevea protease inhibitors against the mycelium growth of Phytophthora palmivora.…”
Section: Introductionmentioning
confidence: 99%
“…In matter of fact, twentyfive percent of the proteins in C-and B-serums are known as antimicrobial agents in H. brasiliensis. Most of these proteins have the activity of chitinase/lysozyme which can degrade fungal and bacterial cell wall components such as chitin and peptidoglycan, respectively (Martin, 1991;Kanokwiroon et al, 2008). Other lutoid-contained proteins such as chitinase, glucanase, hevein, hevamine have antifungal activity against Botrytis cinerea, Fusarium culmorum, Fusarium oxysporum, Phycomyces blakesleeanus, and Trichoderma hamatum (Bokma et al, 2000;Churngchow et al, 1995, Chye & Cheung, 1995, Parijs et al, 1991.…”
Section: Introductionmentioning
confidence: 99%